Pricing decisions of car aggregation platforms in sharing economy: a developing economy perspective. Issue 5 (19th October 2018) - Gupta, Agam; Saha, Biswatosh; Banerjee, Parthasarathi
Abstract Unlike developed economies, developing economies lack surplus assets that have fueled the growth of sharing economy through various digital platforms. In this research, we build a system dynamics model of a ride sharing platform in a developing country that endogenizes the growth of the platform in the presence of stickiness of the asset provider, since platform growth can occur only through new investments in assets that have limited utility outside the platform. Our modeling approach enables capture of two-sided positive network externalities and the same-side negative externalities together in the same framework. Simulations illustrate that the pricing and incentive decisions taken by the platform to overcome the problem of initial asset unavailability have long-term consequences on various parameters of performance of the platform such as driver's profits, platform revenues, and the level of prices of services.